Pembinaan Akhlak Siswa melalui Metode Pembiasaan di Kelas VIII C MTs. Ali Maksum Yogyakarta: Penelitian - Syarwin Dwi Putra (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study attempts to determine the process of implementing student moral development and the obstacles that cause moral deviations. This study uses a descriptive qualitative approach with observation, interview, and documentation methods. Data analysis techniques in this study are: Data reduction, data coding, drawing conclusions. The results of student moral development through the habituation method are quite good, this can be seen from several students who were previously considered to have poor morals, but after moral development through the habituation method, experienced positive behavioral changes. These changes can be seen as students who participate in activities and obey the rules applied by the madrasah, their behavior leads to good things in accordance with religious teachings, including behaving respectfully, disciplined, caring for others, and being generous.